Development Strategy of Navy Base Capability in Realizing Maritime Security of Traffic Separation Scheme Lombok Strait - Herdiawan , Didit; ., Ahmadi (Journal of Ecohumanism, 2024)
Maritime Security means that the maritime area can be controlled, safe, and free from various threats or disturbances. The Indonesian Navy base is part of System Integrated Fleet Weapons (SSAT) which has the function of carrying out maritime security in its working area in the form of operation security sea with deploy all the strength and abilities it has. The Lombok Strait is one of the chokepoints important in The cross voyage south of ALKI II. Enforcement The Lombok Strait Traffic Separation Scheme (TSS) is one of the efforts of the Indonesian government to control the sea in this region. The Indonesian Navy as the driving force organization defense and security maritime, has Denpasar Navy Base and Mataram Navy Base which are adjacent directly to the Lombok Strait TSS. Therefore, that development strategy is needed capability from the second Indonesian Navy Base to realize and guarantee maritime security from various threats like a violation of navigation, violation of law, violation of sovereignty, and threats source Power nature. Determination of development strategy This started with identifying variables that influence the capability Indonesian Navy Base. The next method of modeling System Dynamics uses now reciprocal relationship​ between variables, which is then done simulation model so that the obtained scenario alternative is best. Scenario results from modeling and simulation that have been done, can become a consideration for the leadership of the Indonesian Navy in determining the right and optimal strategy for the development capability of Denpasar and Mataram Indonesian Navy Bases so that capable realize security maritime in TSS Lombok Strait.